Rancang Bangun Sistem Kontrol Irigasi Pintar Berbasis Internet of Things - Slamet Purwo Santosa; Hendrik Pratama (Teknik Elektro Universtias Krisnadwipayana, 2024)
Indonesia is an agricultural country where the majority of the population works as farmers, and Indonesia also has very fertile land to be managed as agricultural land. Where in farming, irrigation or irrigation is very important because irrigation in agricultural fields is a determinant of the success of agricultural products, in this case there are still many Indonesian farmers who have difficulty managing their agricultural irrigation efficiently, where they still have to do irrigation manually on their agricultural fields. So the authors want to provide a solution in the form of smart irrigation based on the internet of things that uses WEMOS D1 as the main device to control input and output to make irrigation automatically when agricultural land is dry by pumping water from rivers or reservoirs around agricultural areas, then connecting to Blynk as a user interface for monitoring agricultural soil moisture, but in this study the authors only made a design in the form of a prototype